Evaluation of a Labelled Bacteriophage with 99mTc as a Potential Agent for Infection Diagnosis - Elena Cardoso, María; Fernández, Leticia; Tejería, Emilia; Esperón, Patricia; Terán, Mariella (Current Radiopharmaceuticals, 2016)
Background and Objective: The design of target-specific molecular imaging probes to determine infection sites are mainly based on the biochemistry of the inflammatory response that may lead to an ideal agent for infection imaging. Infectious diseases timely and specifically diagnosed can be clinically challenging but essential for the patient’s recovery. Laboratory tests can detect the responsible microorganism but cannot discriminate between sterile inflammatory disease and truly infectious disease. On the other hand, scintigraphic images, can pinpoint the infection in the body. Methods: Bacteriophages (phages) are viruses that infect specific bacterial strains. Given the composition of the protein capsid, they could be used as radiopharmaceuticals to diagnose bacterial infection. In this case, PP7 phage was labelled and evaluated as a specific tracer for Pseudomonas aeruginosa infections. 99mTc-Phage synthesis used HYNIC as a bifunctional agent. Physicochemical evaluation included studies such as stability in time, ligand exchange, lipophilicity and bacterial binding assay. Three groups of animals namely; healthy, infected with Pseudomonas aeruginosa and induced sterile inflammation were used to conduct biological evaluation Results: The radiolabelling process required size exclusion purification of the 99mTc-Phage, which was obtained with a radiochemical purity higher than 90%, during 18 hours post labelling. The collective accumulation in the stomach, small intestine and large intestine and thyroid of 99mTc-Phage was negligible, indicating no in vivo reoxidation. The complex presented urinary elimination. Target/ non-target ratio (T/NT) was determined both for sterile inflammation and for infection. Values were 2.5 ± 0.4 and 4.2 ± 0.3 respectively. These values indicate significant differences between sterile inflammation and infection by Pseudomonas aeruginosa (p<0.05 unpaired two sided t-test). Conclusion: Targeted biodistribution profile and good T/NT ratios, indicate that this complex presents enough specificity to discriminate between infection caused by Pseudomonas aeruginosa and sterile inflammation.
Keywords: HYNIC